Competence of Oral Clonidine in Bupivacaine and Dexamethasone Induced Supraclavicular Brachial Plexus Block (The Planet, 2023)
Introduction: The brachial plexus is a web of nerves in the shoulder that suggests drive and sensory signals from the spinal cord to the arms and hands. The motive of the count of adjuvants to local anesthetics for a peripheral nerve block is to have the former onset of sensory and motor block. Methods& Materials: A comparative randomized double-blinded placebo-controlled study was carried out in the Department of Anesthesia, Analgesia, Palliative & Intensive Care Medicine, Dhaka Medical College Hospital, Dhaka from October 2018 to June 2019. A total of 60 patients were fulfilling the criteria. Then informed written consent was taken and data analysis by performed using Statistical Package for the Social Sciences (SPSS) Version 23.0Results: Among the study population (N=60), a tablet of Clonidine100 mcg was given in group A and a Placebo drug was given in group B equally. Around 76.7% were found ASA class I in group A and 83.3% in group B .The mean onset of sensory block & motor block was found 7.6±0.8 &18.3±1.1 minutes in group A respectively and 13.0±1.4 & 18.7±1.8 minutes in group B respectively. After 9 hours, the mean visual analog scale (VAS) score was found 0.03±0.21 in group A and 3.6±1.3 in group B. Conclusion: The use of oral clonidine in supraclavicular brachial plexus block provides quick onset of sensory block. In this outcome, oral clonidine expands the quality of anesthesia and analgesia when it was used as the administration of medication before a treatment or procedure.
Keywords: Clonidine; Brachial Plexus; Analgesics